The Package Says More Than a Thousand Words : The Effect of Eco‐Labelling and Package Material on Consumer's Purchase Intentions - Ollitervo, Virpi; Sipilä, Jenni; Terho, Harri (Wiley, 2026)
This study investigates the influence of two prominent visual packaging cues, eco-labels, and packaging material, on consumers' green purchase intentions in the context of gift-giving, which represents a more complex decision compared to routine consumption. We derive a novel theoretical framework based on signaling theory and cue utilization theory and test our hypotheses with three experiments. The findings reveal that eco-labels and packaging material do not have an interactive effect on purchase intentions. However, an eco-label can indirectly drive purchase intentions through the perceived environmental friendliness of the product (Studies 1, 2, 3). Furthermore, an environmentally friendly packaging material can indirectly affect purchase intentions through both perceived attractiveness of packaging (Studies 1, 2, 3) and perceived environmental friendliness of the product (Studies 1 and 3). The research extends the existing literature at the intersection of green consumption and packaging design by providing novel evidence of the theoretical mechanisms, through which visual packaging cues influence purchase intentions. Furthermore, the study makes a contribution by studying the effects in the previously overlooked context of gift-giving. The implications of the findings are discussed in relation to green marketing and the prevention of greenwashing. Thus, this study provides valuable insights for academics, companies, and regulators interested in fostering green consumption.